2020
DOI: 10.3390/medicina56030095
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hyperuricemia after Kidney Transplantation: Association with Graft Function

Abstract: Background and objectives: In kidney transplant recipients (KTR), hyperuricemia (HU) is a commonly-observed phenomenon, due to calcineurin inhibitors and reduced kidney graft function. Factors predicting HU, and its association with graft function, remains equivocal. Materials and Methods: We conducted a retrospective longitudinal study to assess factors associated with HU in KTR, and to determine risk factors associated with graft function, measured as glomerular filtration rate (GFR). Moreover, GFR > 60 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Recently, Inese Folkmane et al, in 2020, reported that the prevalence of HU in KTxR was 42.36% and its predictors included the presence of cystic diseases, the use of diuretics, and the male gender. Therefore, being a younger, female, with a normal BMI increased the possibility of normal GFR [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Inese Folkmane et al, in 2020, reported that the prevalence of HU in KTxR was 42.36% and its predictors included the presence of cystic diseases, the use of diuretics, and the male gender. Therefore, being a younger, female, with a normal BMI increased the possibility of normal GFR [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malheiro et al found that hyperuricemic patients were overwhelmingly male of 302 renal transplant patients ( 22 ). This gender bias could be explained by the fact that estrogenic compounds enhance renal urate excretion in women, possibly reducing the active renal urate transporters resulting in less tubular UA reabsorption ( 7 , 23 ).…”
Section: Risk Factors For Hua After Renal Transplantationmentioning
confidence: 99%
“…Since, there is not much evidence to prove that the use of beta blockers is a risk factor for HUA after renal transplantation, a detailed mechanism needs further investigation. Multiple studies have reported that diuretics were directly related to a higher risk for HUA after renal transplantation ( 7 , 8 , 32 ). Among these, thiazide diuretics and loop diuretics can interact with renal OAT; they enter the proximal tubular cells from the blood by OAT1 and OAT3, which could probably compete with UA, causing the reduced secretion of UA ( 30 , 44 , 45 ).…”
Section: Risk Factors For Hua After Renal Transplantationmentioning
confidence: 99%
“…This study has several limitations. First, we cannot exclude, that in some patients' body the native vein graft will be rejected or vasodilation will occur faster, than using the prosthetic graft, which will depend on individual reaction to the new structure in the forearm compartment, hypoxia, nutrition, different growth factor (plateletderived growth factor, vascular endothelial growth factor) activity, the presence or lack of everyday physical activity, changes in body temperature, hypotension et cetera [9,10,12]. A second limitation, we had no possibility to perform the procedure clinically on the patient due to the limited access to the hospital and lack of the researches, in which the great saphenous vein was used as arteriovenous anastomosis connective structure, except cardiovascular surgery researches with the saphenous vein in coronary bypass surgery [1].…”
Section: Limitations Of the Studymentioning
confidence: 99%